Pengaruh Kepuasan Kerja Terhadap Turnover Intention Cabin Crew Maskapai X dengan Organizational Commitment dan Intent to Stay Sebagai Variabel Mediasi [Effect of Job Satisfaction on Turnover Intention of Airline Crew on X Airline with Organizational Commitment and Intent to Stay as the Mediating Variable] - Tantrianto, Yogie; Meilani, Yohana F. Cahya Palupi (Feedforward: Journal of Human Resource, 2021)
This study was conducted to determine the effect of job satisfaction on the turnover intention of airline crew on X airline with organizational commitment and intent to stay as the mediating variable. This study uses a quantitative method, using convenience sampling technique to determine the sample of airline X airline cabin crew throughout Indonesia who are still actively contracted and working for airline X, this airline is under the auspices of PT Lion Mentari Airlines. There were 85 cabin crew whose data were successfully collected through a questionnaire distributed on google form. The data that has been collected is processed with PLS SEM using program SmartPLS software. The results showed that job satisfaction has an influence on organizational commitment, organizational commitment has an influence on intent to stay, job satisfaction has an influence on turnover intention, and job satisfaction has an influence on turnover intention of airline crew cabin X with organizational commitment and intent to stay as the mediating variable. The managerial implication of this research suggests that airline X can make efforts to improve cabin crew job satisfaction in order to increase organizational commitment and intent to stay and reduce the turnover intention of cabin crew.BAHASA INDONESIA ABSTRACT:Penelitian ini dilakukan untuk mengetahui pengaruh kepuasan kerja terhadap turnover intention cabin crew maskapai X dengan organizational commitment dan intent to stay sebagai variabel mediasi. Penelitian ini menggunakan metode kuantitatif, dengan menggunakan teknik convenience sampling untuk penentuan sampel kepada para cabin crew maskapai penerbangan X di seluruh Indonesia yang masih aktif dikontrak dan bekerja di maskapai penerbangan X. Maskapai ini berada di bawah naungan PT Lion Mentari Airlines. Terdapat 85 cabin crew yang berhasil dikumpulkan datanya melalui kuesioner yang disebar dengan google form. Data yang telah dikumpulkan diolah dengan alat statistik PLS-SEM dengan program SmartPLS. Hasil penelitian menunjukkan bahwa kepuasan kerja memiliki pengaruh terhadap organizational commitment, organizational commitment memiliki pengaruh terhadap intent to stay, kepuasan kerja memiliki pengaruh terhadap turnover intention, dan kepuasan kerja memiliki pengaruh terhadap turnover intention cabin crew maskapai penerbangan X dengan organizational commitment dan intent to stay sebagai variabel mediasi. Implikasi manajerial dari penelitian ini disarankan maskapai X dapat melakukan upaya untuk meningkatkan kepuasan kerja cabin crew supaya dapat meningkatkan organizational commitment dan intent to stay serta mengurangi tingkat turnover intention dari cabin crew.